2021
DOI: 10.21601/ejbms/11285
|View full text |Cite
|
Sign up to set email alerts
|

Can COVID-19 Be a Potential Risk Factor for Voriconazole-Induced Hyperkalemia?

Abstract: Voriconazole is an antifungal agent that is commonly used to treat fungal infections. Like any drug, it can cause side effects, especially in the case of overdose. Few cases of hyperkalemia have been reported, which presented when the serum voriconazole level was elevated or when there was voriconazole-drug interaction. We present here a case of voriconazole-induced hyperkalemia, prescribed for an oral candidiasis due to Candida glabrata in a patient hospitalized for severe COVID-19 pulmonary infection. Inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…However, there are contradicting findings on concurrent use of voriconazole and lopinavir/ritonavir, as some studies have found that the area under the concentration-time curve (AUC) and maximum concentration ( C max ) of voriconazole decreased; while, other studies have shown an unexpected increase in voriconazole concentration when co-administered with lopinavir/ritonavir in patients with COVID-19 [ 104 ]. Voriconazole can induce severe hyperkalaemia in patients with COVID-19 with severe inflammation, when serum voriconazole level was elevated or when voriconazole–drug interaction occurs [ 105 ]. Among the experimental COVID-19 therapies, voriconazole was found to interact with atazanavir and hydroxychloroquine [ 106 ].…”
Section: Drugs Used To Treat Covid-19mentioning
confidence: 99%
“…However, there are contradicting findings on concurrent use of voriconazole and lopinavir/ritonavir, as some studies have found that the area under the concentration-time curve (AUC) and maximum concentration ( C max ) of voriconazole decreased; while, other studies have shown an unexpected increase in voriconazole concentration when co-administered with lopinavir/ritonavir in patients with COVID-19 [ 104 ]. Voriconazole can induce severe hyperkalaemia in patients with COVID-19 with severe inflammation, when serum voriconazole level was elevated or when voriconazole–drug interaction occurs [ 105 ]. Among the experimental COVID-19 therapies, voriconazole was found to interact with atazanavir and hydroxychloroquine [ 106 ].…”
Section: Drugs Used To Treat Covid-19mentioning
confidence: 99%